Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1096/fj.201700667r
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fibroblast growth factor 23 (FGF23) signaling rescues renal anemia

Abstract: Severe anemia and iron deficiency are common complications in chronic kidney disease. The cause of renal anemia is multifactorial and includes decreased erythropoietin (Epo) production, iron deficiency, and inflammation, and it is currently treated with injections of synthetic Epo. However, the use of recombinant Epo has several adverse effects. We previously reported that high fibroblast growth factor 23 (FGF23) levels in mice are associated with decreased red blood cell production, whereas genetic inactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 70 publications
6
107
2
Order By: Relevance
“…7A-C). We previously reported that treatment with the FGF23 C-tail blocking peptide significantly increases circulating Epo levels in mice (29). Here, we confirmed this effect in mice injected with LPS or saline (Fig.…”
Section: Inhibition Of Fgf23 Signaling Increases Renal and Extra-renasupporting
confidence: 87%
See 4 more Smart Citations
“…7A-C). We previously reported that treatment with the FGF23 C-tail blocking peptide significantly increases circulating Epo levels in mice (29). Here, we confirmed this effect in mice injected with LPS or saline (Fig.…”
Section: Inhibition Of Fgf23 Signaling Increases Renal and Extra-renasupporting
confidence: 87%
“…Here, we confirmed this effect in mice injected with LPS or saline (Fig. 7D) using a 10 times lower concentration of the FGF23 C-tail blocking peptide than the one we used in (29). However, we found that 4 hours of LPS treatment at the concentration of 50 µg/kg were not sufficient to alter circulating Epo levels (Fig.…”
Section: Inhibition Of Fgf23 Signaling Increases Renal and Extra-renasupporting
confidence: 69%
See 3 more Smart Citations